2014
DOI: 10.1002/mrm.25463
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative mapping of cerebral metabolic rate of oxygen (CMRO2) using quantitative susceptibility mapping (QSM)

Abstract: Purpose To quantitatively map cerebral metabolic rate of oxygen (CMRO2) and oxygen extraction fraction (OEF) in human brains using quantitative susceptibility mapping (QSM) and arterial spin labeling measured cerebral blood flow (CBF) before and after caffeine vasoconstriction. Methods Using the multiecho 3D gradient echo sequence and an oral bolus of 200 mg caffeine, whole brain CMRO2 and OEF were mapped at 3mm isotropic resolution on 13 healthy subjects. The QSM based CMRO2 was compared with an R2* based C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
211
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 134 publications
(218 citation statements)
references
References 73 publications
6
211
1
Order By: Relevance
“…Therefore, CBF in the ROI is lower than in the gray matter. 28 suggesting the robustness of these methods for the measurement of OEF and CMRO 2 .…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, CBF in the ROI is lower than in the gray matter. 28 suggesting the robustness of these methods for the measurement of OEF and CMRO 2 .…”
Section: Discussionmentioning
confidence: 94%
“…23 Briefly, the present QSM-based method has several advantages, such as use of a conventional sequence; short acquisition time; no need for any challenge, contrast agent, or other invasive procedures; sufficient spatial resolution with wholebrain coverage; and robustness to low perfusion status, suggesting high ease of use in clinical practice and clinical studies for patients with cerebrovascular and other neurologic disorders. 23 Zhang et al 19 have recently demonstrated that QSM can be used with perfusion measurements of pre-and post-caffeine vasoconstriction to map the cerebral metabolic rate of oxygen and OEF. However, this method needs a caffeine challenge and 2 MR images.…”
Section: Discussionmentioning
confidence: 99%
“…18 In general, these techniques use blood oxygen level-dependent effects induced by differences in magnetic susceptibility between oxy-and deoxyhemoglobin to quantify oxygenation in venous structures and/or brain parenchyma. [19][20][21] Quantitative susceptibility mapping (QSM) is a postprocessing technique for quantifying the magnetic susceptibility of venous structures and brain parenchyma from T2*-weighted magnitude/phase images, which can be easily obtained by commercial scanners. 22 Indeed, a recent study has introduced an OEF measurement method based on the QSM technique and has demonstrated that cerebral OEF images generated from QSM at 7T MR imaging correlate with OEF images on PET and provide high sensitivity and high specificity for detecting misery perfusion in the middle cerebral artery territory in patients with unilateral chronic ICA or MCA steno-occlusive disease.…”
mentioning
confidence: 99%
“…where CBF is the cerebral blood flow (mL=100 g=min); and ½dH v and ½dH a are the deoxyheme molar [2], and subsequently CMRO 2 , can be mapped using QSM (19,20).…”
Section: Reconstruction Of Cmro 2 and Oefmentioning
confidence: 99%
“…Unlike R 2 and R Ã 2 , the relationship between [dH] and tissue susceptibility is linear in its concentration and independent of imaging parameters (11)(12)(13). Hence, QSM can be used to quantify oxygenation in large veins (14)(15)(16)(17)(18) and in tissue (19,20). The [dH] in tissue can be determined from QSM by compensating for contribution from non-heme iron, such as those stored in ferritin.…”
Section: Introductionmentioning
confidence: 99%